Respostas
respondido por:
3
Método da Adição:
2x + 3y = 0 (3)
3x + 5y = 2 ( - 2)
6x + 9y = 0
- 6x - 10y = - 4 (+)
--------------------------
- y = - 4 ( - 1)
y = 4
2x + 3y = 0
2x + 3.4 = 0
2x + 12 = 0
2x = - 12
x = -12/2
x = - 6
2x + 3y = 0 (3)
3x + 5y = 2 ( - 2)
6x + 9y = 0
- 6x - 10y = - 4 (+)
--------------------------
- y = - 4 ( - 1)
y = 4
2x + 3y = 0
2x + 3.4 = 0
2x + 12 = 0
2x = - 12
x = -12/2
x = - 6
mayrakailanny:
Muito obrigadoo!! valeu :)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás